Impact of robotic access on outcomes after lung cancer surgery in France: Analysis from the Epithor databaseCentral MessagePerspective - Leslie Madelaine, MD; Jean-Marc Baste, MD, PhD; Delphine Trousse, MD, PhD; Renaud Vidal, MD; Marion Durand, MD; Pierre-Benoit Pagès, MD, PhD (JTCVS Open, 2023)
Introduction: We aimed to compare postoperative outcomes after pulmonary resection for lung cancer after open thoracotomy (OT), video-assisted (VATS), and robotic-assisted (RA) thoracic surgery using a propensity score analysis. Methods: From 2010 to 2020, 38,423 patients underwent resection for lung cancer. In total, 58.05% (n = 22,306) were operated by thoracotomy, 35.35% (n = 13,581) by VATS, and 6.6% (n = 2536) by RA. A propensity score was used to create balanced groups with weighting. End points were in-hospital mortality, postoperative complications, and length of hospital stay, reported by odds ratios (ORs) and 95% confidence intervals (CIs). Results: VATS decreased in-hospital mortality compared with OT (OR, 0.64; 95% CI, 0.58-0.79; P < .0001) but not compared with RA (OR, 1.09; 95% CI, 0.77-1.52; P = .61). VATS reduced major postoperative complications compared with OT (OR, 0.83; 95% CI, 0.76-0.92; P < .0001) but not RA (OR, 1.01; 95% CI, 0.84-1.21; P = .17). VATS reduced prolonged air leaks rate compared with OT (OR, 0.9; 95% CI, 0.84-0.98; P = .015) but not RA (OR, 1.02; 95% CI, 0.88-1.18; P = .77). As compared with OT, VATS and RA decreased the incidence of atelectasis (respectively: OR, 0.57; 95% CI, 0.50-0.65; P < .0001 and OR, 0.75; 95% CI, 0.60-0.95; P = .016); the incidence of pneumonia (OR, 0.75; 95% CI, 0.67-0.83; P < .0001 and OR, 0.62; 95% CI, 0.50-0.78; P < .0001); and the number of postoperative arrhythmias (OR, 0.69; 95% CI, 0.61-0.78; P < .0001 and OR, 0.75; 95% CI, 0.59-0.96; P = .024). Both VATS and RA resulted in shorter hospital stays (−1.91 days [−2.24; −1.58]; P < .0001 and −2.73 days [−3.1; −2.36]; P < .0001, respectively). Conclusions: RA appeared to decrease postoperative pulmonary complications as well as VATS compared with OT. VATS decreased postoperative mortality as compared with RA and OT.